Comparison of Isolation, Expansion and Cryopreservation Techniques to Produce Stem Cells from Human Exfoliated Deciduous Teeth (SHED) with Better Regenerative Potential - Lee, Sau H.; Looi, Chung Y.; Chong, Pei P.; Foo, Jhi B.; Looi, Qi H.; Ng, Chu X.; Ibrahim, Zaidah (Current Stem Cell Research & Therapy, 2021)
Mesenchymal Stem Cells (MSCs) are adult stem cells that are gaining worldwide attention for their multi-potential use in tissue engineering-based regenerative medicine. They can be obtained from numerous sources and one of the excellent sources is the dental tissue, such as Stem cells that are extracted from the Human Exfoliated Deciduous teeth (SHED). SHED are considered ideal due to their inherent characteristics, including the capability to proliferate quickly with minimal oncogenesis risk, multipotency capacity and their ability to suppress the immune system. On top of these positive cell traits, SHED are easily accessible with the patient’s safety assured, posing less ethical issues and could also provide a sufficient number of cells for prospective clinical uses. This is primarily attributed to their ability to differentiate into multiple cell linages, including osteoblasts, odontoblasts, neuronal cells, adipocytes, as well as endothelial cells. Albeit SHED having a bright future, there still remains an obstacle to develop reliable experimental techniques to retain the long-term regeneration potential of the stem cells for prospective research and clinical applications. Therefore, this review aims to describe the various isolation, expansion and cryopreservation techniques used by researchers in this stem cell field. Optimization of these techniques is crucial to obtain distinct SHED culture with preserved stem cell properties, which enable more reproducible results that will be the key for further stem cell therapy development.
Keywords: expansion technique